2015
DOI: 10.1111/ane.12536
|View full text |Cite
|
Sign up to set email alerts
|

A video-oculographic study of acute vestibular syndromes

Abstract: Early video head impulse testing in the emergency department and each day of admission is feasible and well tolerated. There is marked variation in VOR gain in patients with symptoms and signs of VN, and low initial VOR gains are a predictor for low VOR gains on subsequent days. Improvement in VOR gains was seen in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Overt saccades, as secondary catch-up saccades, are generated when the covert saccades fail to drive eye-movements reaching the target during head rotation. In line with previous study, our study found a certain number of patients presenting with covert saccades at early stage of VN ( 39 ). Therefore, the incidence and parameters of saccades, covert or overt, are a promising indicator for evaluation of vestibular deficit and central compensation other than VOR ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overt saccades, as secondary catch-up saccades, are generated when the covert saccades fail to drive eye-movements reaching the target during head rotation. In line with previous study, our study found a certain number of patients presenting with covert saccades at early stage of VN ( 39 ). Therefore, the incidence and parameters of saccades, covert or overt, are a promising indicator for evaluation of vestibular deficit and central compensation other than VOR ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not track their vHITs in the early stages in this study. By sequentially measuring the VOR gains of patients with acute VN, previous studies have found the ipsilesional VOR gains vary after the initial measurement during the week from onset ( 38 , 39 ). Meanwhile, patients with lower initial VOR gains were less likely to improve on subsequent 3–5 days, and would generate more covert catch-up saccades over time ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В таких случаях необходимо проведение видеоимпульсного теста, более известного как vHIT,более чувствительного и объективного метода, позволяющего оценить функцию каждого из полукружных каналов и количественно определить дефицит ВОР с пораженной стороны. Принцип проведения исследования остается таким же, как и при пробе Хальмаги, однако оценка скорости поворота головы и глаз проводится встроенным в прибор гироскопом и высокочастотной камерой соответственно [30].…”
Section: оценка и характеристики нистагма при внunclassified
“…Recently it has been argued that SHIMP gives more precise information on the VOR slow phase velocity value compared to HIMP because the evaluation of the gain is not affected by covert saccades [ 9 , 10 ]. Several studies [ 11 , 12 ] have already suggested the use of vHIT with HIMP to diagnose a VN in the acute phase and as a valid tool to diagnose peripheral vestibulopathy in the different stages of the disease [ 3 ]. A recent systematic review [ 13 ] highlighted the usefulness of the SHIMP in diagnosing a VOR alteration in patients with vestibulopathy suggesting to evaluate with new studies if this new paradigm could replace the HIMP in both the acute and chronic phases of vestibulopathy.…”
Section: Introductionmentioning
confidence: 99%